Geochemical Features of the Thermal and Mineral Waters From the Apuseni Mountains (Romania) - Nicula, Alin-Marius; Ionescu, Artur; Pop, Ioan-Cristian; Roba, Carmen; Forray, Ferenc L.; Orăşeanu, Iancu; Baciu, Călin (Frontiers in Earth Science, 2021)
The Apuseni Mountains are located between the large geothermal area of the Pannonian Basin and the low thermal flux Transylvanian Basin. Thermal and mineral waters have been sampled from 42 points along a NW-SE transect. The general chemistry and the water isotope (deuterium and oxygen-18) composition were analyzed. Most of the thermal aquifers are located in carbonate reservoirs. The waters mainly belong to the Ca-HCO3 hydrochemical type, excepting the western side, towards the Pannonian Basin, where the Na-HCO3 type may occur. The isotope composition indicates aquifer recharge from precipitation. The geochemical characteristics and the structural position of the study area suggest two distinct geothermal contexts. The Southern Apuseni area geothermal features are likely to be connected to the Neogene – Early Quaternary magmatic activity from the Mureș Valley and Zarand Depression. The geothermal manifestations in the north-western part of the study area, at the border between the Northern Apuseni and the Pannonian Depression, share features of the latter one.